Students’ and teachers’ perceptions of school based scientific literacy priorities and practice: A cross‐cultural comparison between Cyprus and Germany. - Schulte, Theresa; Bolte, Claus; Kyza, Eleni A.; Georgiou, Yiannis (My University, 2013)
Scientific literacy is an issue of paramount importance in every modern society. However, when it comes to public understanding, it seems that there is no consensus regarding what aspects should be addressed within the regular science education curriculum or how scientific literacy should be promoted. Additionally, despite the fact that teachers and students are the main stakeholders in each educational system, their voices are usually neglected. In this context, the present study employed a Delphi approach, seeking to investigate empirically the extent of any consensus between students and teachers in Germany and Cyprus, comparing their assessments regarding what science education aspects should be prioritized as well as in which extent these aspects are currently practiced. The outcome of this cross-cultural research revealed that except some minor differences, students and teachers in both countries perceive in general large discrepancies between a desired status and the status quo in science education. More specifically, science education, as currently practiced, was defined by elements from the “classic” scientific disciplines giving much emphasis on content as well as on the promotion of conceptual understanding. On the other hand, many of the greater aims of general science-related education that students and teachers gave priority to, such as the relation of science with students„ interests and everyday life or the development of inquiry skills, are only rarely taken up in science classes. Following this reasoning, future educational reforms in both countries should do well to invest more efforts in order to bridge this gap between priority and praxis.
Keywords: Curricular Delphi study; Scientific literacy; Stakeholders; Cross-cultural comparison; PROFILES